2013
DOI: 10.1016/j.jagp.2012.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Association of Five-Factor Model Personality Domains and Facets with Presence, Onset, and Treatment Outcomes of Major Depression in Older Adults

Abstract: Objectives To assess the relationship of multiple domains and facets of the five factor model of personality with presence, onset, and severity of late life depression. Design Cross-sectional analysis of depression status, and age of onset. Retrospective analysis of baseline severity. Longitudinal analysis of severity after 3 and 12 months of psychiatric treatment. Setting: Private university-affiliated medical center in the Southeastern US. Participants One hundred twelve psychiatric patients with a curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
49
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 39 publications
8
49
1
1
Order By: Relevance
“…The present findings replicate and extend existing evidence for the impact of neuroticism, and VS specifically, on both treatment response and cognitive decline in LLD (18, 19). The current findings demonstrate a clinically meaningful 10-point difference in global cognition between high and low VS LLD subjects at 10 years.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The present findings replicate and extend existing evidence for the impact of neuroticism, and VS specifically, on both treatment response and cognitive decline in LLD (18, 19). The current findings demonstrate a clinically meaningful 10-point difference in global cognition between high and low VS LLD subjects at 10 years.…”
Section: Discussionsupporting
confidence: 86%
“…Our preliminary evidence indicated high total neuroticism and the VS trait were the only neuroticism scores associated with both a worse one-year antidepressant treatment response and a two-year decline in global cognitive functioning in LLD (18, 19). Elsewhere, increased VS and anxiety were the only neuroticism traits associated with global cognitive decline in non-depressed older adults followed over three years (11).…”
Section: Objectivementioning
confidence: 73%
See 1 more Smart Citation
“…It aims to empirically describe personality along five major dimensions, namely neuroticism, extraversion, openness, agreeableness, and conscientiousness [4,5]. These five personality dimensions show clear heritable characteristics [6,7] and have been shown to be associated with different psychiatric disorders such as anxiety, depressive, substance use, and personality disorders [8,9,10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…Three such studies [20,21,22] reported a greater increase (relative to controls) of neuroticism in EOD than in LOD, and three [23,24,25] found equal increases of neuroticism in EOD and LOD. Two of the studies employed a methodologically strong community-based longitudinal prospective design with personality measures predicting depressive episodes 3-5 years [20] and 10 years [22] later.…”
Section: Introductionmentioning
confidence: 99%